Advantages of treatment of chronic generalized periodontitis with Bepanten ointment containing propolis (Eurasian Research Bulletin, 2022)
This article discusses the benefits of including propolis-containing ointment in complex therapeutic measures when generalized periodontitis is combined with cardiovascular diseases